The Influence of Economic Growth, Minimum Wages, and Average Years of Schooling on the Unemployment Rate in NTB 2015-2024 - Destina Marlina; Akung Daeng; Tuti Handayani (Future Techno-Science, 2025)
In the current era, the high unemployment rate is a serious problem that must be addressed immediately by the government. The rising unemployment rate in West Nusa Tenggara can hinder the development programs implemented by the government. The purpose of this research is to examine the impact of economic growth, minimum wage, and average years of schooling on the unemployment rate in West Nusa Tenggara from 2015 to 2024. The analytical tools used are panel data regression with the Fixed Effect Model, partial t-test, simultaneous F-test, coefficient of determination (R2) test, and classical assumption tests including autocorrelation, multicollinearity, and heteroscedasticity. The results of this study show that. The economic growth variable has a negative and significant impact on the open unemployment rate. Meanwhile, the minimum wage variable is not significant, meaning the minimum wage does not have a substantial effect on the open unemployment rate. The average length of schooling variable has a positive and significant impact on the unemployment rate.